Increased mean corpuscular haemoglobin concentration: artefact or pathological condition?. (27th August 2016) - Berda‐Haddad, Y.; Faure, C.; Boubaya, M.; Arpin, M.; Cointe, S.; Frankel, D.; Lacroix, R.; Dignat‐George, F.
Summary: Introduction: In daily practice in haematology laboratories, spurious increased MCHC induces an analytical alarm and needs prompt corrective action to ensure delivery of the right results to the clinicians. The aim of this study was to establish a 'decision tree' using the new parameters red blood cells (RBC‐O) and haemoglobin (HGB‐O) from the Sysmex XN‐10 RET obtained by flow cytometry to deliver appropriate results. Methods: From 128 unknown patients with MCHC > 365 g/L, all erythrocyte parameters including reticulocyte parameters were measured and analysed in parallel with blood smears, chemistry index and osmolarity. Differences between optical parameters (RBC‐O, HGB‐O) and usual parameters (RBC, HGB) obtained by impedance and photometry were reported also. Results: Four groups were defined from observations: ‐RBC agglutination ( n = 22); ‐optical interference ( n = 17); ‐RBC disease ( n = 18); and ‐others ( n = 71). The use of RBC‐O and HGB‐O permitted efficient correction of the abnormalities when RBC agglutination and/or optical interference were present in 36 of 39 patients. Reticulocyte parameters permitted to elaborate an RBC score that allowed a highly sensitive detection of RBC disease patients (17/18). Conclusion: Based on new parameters, we propose a 'decision tree' that delivers time savings and supports biological interpretation in case of elevated MCHC.